Pengaruh Gender Stereotyping Terhadap Kepuasan Hidup Perempuan yang Tidak Berpenghasilan - Djalle, Jauza Kamil; Muhammad Nur Hidayat Nurdin; Perdana Kusuma; Hildawati (Musawa: Journal for Gender Studies, 2025)
Women are expected to behave according to the gender roles that have been determined by culture. These gender roles give rise to generalizations about the characteristics that women should and should not possess. This, in turn, affects the life satisfaction of women. This study aims to determine the influence of gender stereotyping on the life satisfaction of non-income-earning women. The research method used is quantitative. Data collection was carried out using two scales: the gender stereotyping scale and the life satisfaction scale. The sample in this study consisted of 68 non-income-earning women, aged 18 to 25 years, residing in Makassar City. The results of the hypothesis test using Spearman’s rho indicate an influence of the agency dimension on the life satisfaction of non-income-earning women, with a significance value of 0.000 < 0.05. Meanwhile, there was no significant influence of the communality dimension on the life satisfaction of non income-earning women, with a significance value of 0,189 > 0,05. The implications of this research provide an understanding of the importance of gender stereotyping, particularly in relation to agency, as one of the factors influencing life satisfaction, especially for women without income.